2009
DOI: 10.3855/jidc.56
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Salmonella and Shigella from fish harvested from the Winam Gulf of Lake Victoria, Kenya

Abstract: Background: Human infections caused by pathogens transmitted from fish are quite common. The aim of this study was to isolate enteric pathogenic bacteria from fish that might be transmitted to humans after the handling or consumption of such fish. Methodology: One hundred and twenty Nile tilapia fish harvested using various fishing methods were collected from fishermen in five fish landing beaches within Winam Gulf and disinfected externally using 70% ethyl alcohol for 2 minutes then washed three times with au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 12 publications
2
17
0
3
Order By: Relevance
“…The isolation of Proteus spp. from fish has also been reported in former studies (David et al, 2009;Lopez-Sabater et al, 1996). Yagoub, (2009, isolated Proteus spp.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The isolation of Proteus spp. from fish has also been reported in former studies (David et al, 2009;Lopez-Sabater et al, 1996). Yagoub, (2009, isolated Proteus spp.…”
Section: Resultsmentioning
confidence: 66%
“…in fish have been reported as 2.4%, and 10.8% respectively (Yagoub, 2009). Adededji andİbrahim, 2011, andDavid et al, 2009 have also reported contamination of shrimp and fish with E. aerogenes. The present study, the percentage of isolated Citrobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…David, Wandili, Kakai, and Waindi (2009), recently described the isolation of Salmonella from fish harvested in Lake Victoria, Kenya, which supports the most productive freshwater fishery in the world. Bouchrif et al (2009) found Salmonella in 10 out of 526 seafood products analyzed in Morocco between 2002 and 2005 (Table 3).…”
Section: Data From India and Other Asian Countriesmentioning
confidence: 99%
“…E. coli isolated from Oreochromis niloticus with an incidence of (17.5%) as shown in (Table 3).These results partial agree with Saqr et al (2016) reporting incidences (18.3%). Higher incidences of E.coli were recovered by Amr et al (2012), David et al (2009), Galal et al (2013)and Gupta et al (2013) who reported incidences of E. coli 50%, 57.1%,29.34% and 36% respectively. But Atwa (2017) isolated E. coli from skin, muscle, intestine and liver with incidences 25, 22.5, 25 and 35% respectively.…”
Section: DI 4 Discussionmentioning
confidence: 85%